1980
DOI: 10.1063/1.440737
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on vibrational phase relaxation and frequency shifts in isobutylene

Abstract: The Raman line shapes and frequencies of the ν4 asymmetric (C=CH2) stretching mode at 1657 cm−1 and the ν9 symmetric (C–CH3) stretching mode at 805 cm−1 (both of symmetry A1) have been measured in dilute solutions of isobutylene in several polar and nonpolar solvents. The frequency shifts in the different solutions can be interpreted in terms of repulsion, dispersion, induction, and dipolar forces between molecular bonds. The induction and dipolar forces play only a minor role. The blue shift due to the repuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…The variation in Raman peak position with PT reflects interactions between molecules. As noted above, dominance of attractive forces leads to a shift in the Raman peak position to lower wave numbers whereas dominance of repulsive forces leads to a shift in the Raman peak position to higher wave numbers . The reason for this is that dominance of repulsive forces contracts the bond length slightly whereas dominance of attractive forces expands the bond length slightly .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The variation in Raman peak position with PT reflects interactions between molecules. As noted above, dominance of attractive forces leads to a shift in the Raman peak position to lower wave numbers whereas dominance of repulsive forces leads to a shift in the Raman peak position to higher wave numbers . The reason for this is that dominance of repulsive forces contracts the bond length slightly whereas dominance of attractive forces expands the bond length slightly .…”
Section: Discussionmentioning
confidence: 74%
“…Raman peak positions of fluids have been shown to vary as functions of pressure, temperature, and density . Shifts in the Raman peak position of fluids with changing conditions have been related to the attractive and repulsive forces between molecules: attractive forces cause Raman peak position to shift to lower wave number, whereas repulsive forces cause Raman peak position to shift to higher wave number, and the overall direction of peak shift with changing conditions implies dominance of either attractive or repulsive forces …”
Section: Introductionmentioning
confidence: 99%
“… 20 This weakens the forces between neighboring atoms, yielding lower covalent and ionic bond strengths. 62 , 63 …”
Section: Results and Discussionmentioning
confidence: 99%
“…There are, however, some points of conceptual contact with the 13 C KIE measurements reported herein and studies upon vibrational frequency shifts observed as a function of pressure. Frequencies corresponding largely to CC single‐bond stretches are almost exclusively blueshifted upon the application of pressure 51. 52 However, heavy‐atom bonds with significant dipoles, such as the CF bond in CFCl 3 , the CC bond in CH 2 CCl 2 , and the CN bond in CH 3 CN are redshifted over a significant portion of the pressure range explored.…”
Section: Enantioselective Reductionsmentioning
confidence: 99%